2018
DOI: 10.1590/0101-6628.133
|View full text |Cite
|
Sign up to set email alerts
|

Contrarreforma do Estado e gerencialismo: novo fetiche, velha proposta

Abstract: Resumo: Este artigo debate as transformações do mundo do trabalho sob a égide dos organismos multilaterais, dando ênfase à disseminação do ideário gerencial no setor público, espaço privilegiado de atuação do assistente social. Realizamos um levantamento bibliográfico do pensamento social crítico, bem como documental do Judiciário trabalhista carioca enquanto espaço sócio-ocupacional reestruturado. Conclui-se que essa conjuntura inflexiona a tradição progressista do Serviço Social brasileiro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
2
0
3
Order By: Relevance
“…A crise do capital, processo fabricado pelos próprios detentores do capital, que opera por meio de choques intensos para aumentar suas margens de lucro, afeta o Brasil e rebate nas políticas públicas sociais na atualidade (Bento, 2003;Sousa;Patriota, 2006;Valle;Leite, 2018). Essa crise seria decorrente dos ataques desferidos pelos agentes neoliberais que estão a serviço do capital financeiro, instalados nas grandes empresas e no mercado em geral, operando nos meios de comunicação, nas escolas e universidades privadas, no aparelho de Estado e na também na própria universidade pública.…”
Section: O Gerenciamento Empresarial Da Política No Estado Neoliberalunclassified
See 2 more Smart Citations
“…A crise do capital, processo fabricado pelos próprios detentores do capital, que opera por meio de choques intensos para aumentar suas margens de lucro, afeta o Brasil e rebate nas políticas públicas sociais na atualidade (Bento, 2003;Sousa;Patriota, 2006;Valle;Leite, 2018). Essa crise seria decorrente dos ataques desferidos pelos agentes neoliberais que estão a serviço do capital financeiro, instalados nas grandes empresas e no mercado em geral, operando nos meios de comunicação, nas escolas e universidades privadas, no aparelho de Estado e na também na própria universidade pública.…”
Section: O Gerenciamento Empresarial Da Política No Estado Neoliberalunclassified
“…Já a psicanálise do campo de Freud e Lacan (Elia, 2004;Garcia--Roza, 2009) postula que o ser humano vivencia um complexo processo de subjetivação ou de constituição da subjetividade, processo que estrutura a subjetividade ou a realidade psíquica sob a forma de modalidades diversas (recalcamento, foraclusão, renegação), propensas a impasses variados (Lacan, 1979(Lacan, , 1998. Essa perspectiva é importante, pois, entre muitas outras questões relevantes, permite a superação de inúmeras dicotomias que pululam no campo psi: interno/externo; psíquico/orgânico; comportamento/vivências subjetivas; natural/social; autonomia/determinação; doença-cura etc.…”
Section: Considerações Críticas Intercessoras Para Fundamentar a Aten...unclassified
See 1 more Smart Citation
“…Thus, it is believed that NPM, in particular its managerialist side, has induced transformations in higher education and on nursing professors' conceptions and practices, cluttering those practices that align with dialectical theory, and supporting those that align with neoliberal assumptions, that is, hindering the advancement of progressive perspectives, which has also been happening and reported in a study in the area of social assistance. 29 Also in this study, it was found that the managerial university gets the nursing professor increasingly trapped in the production of what the university and the postgraduate regulatory agencies demand and is in line with the thought that NPM in the university comes to control it in the perspective and vigilance of 'managers' about how professionals work at the university, the content and type of 11/14 their work, since it focuses on the dissemination of ideas that support the neoliberal consolidation in the university, based on market perspectives and desires. [29][30] This aspect is very relevant because it associates the CAPES model of evaluation with the process of implementation of management devices that affect the university and nursing teaching, making the resistance to this model complex.…”
Section: /14mentioning
confidence: 99%
“…29 Also in this study, it was found that the managerial university gets the nursing professor increasingly trapped in the production of what the university and the postgraduate regulatory agencies demand and is in line with the thought that NPM in the university comes to control it in the perspective and vigilance of 'managers' about how professionals work at the university, the content and type of 11/14 their work, since it focuses on the dissemination of ideas that support the neoliberal consolidation in the university, based on market perspectives and desires. [29][30] This aspect is very relevant because it associates the CAPES model of evaluation with the process of implementation of management devices that affect the university and nursing teaching, making the resistance to this model complex. The main limitation of this research, which also becomes an object of consideration in future research, reveals the non-inclusion of students' view in the production of data.…”
Section: /14mentioning
confidence: 99%